2013
DOI: 10.1103/physreva.87.043420
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Doppler cavity cooling beyond the Lamb-Dicke regime

Abstract: We investigate the dynamics of cavity cooling of a single ion beyond the Lamb-Dicke regime and demonstrate a cooling limit of approximately 50% of the Doppler temperature using a high finesse cavity for the first time. We also study the statistical properties of the ion-cavity emission and present a model that maps the phonon states to the photon states. With this model, we explain the super-Poissonian photon distribution observed in our experiments and propose a method to estimate the ion temperature in a rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Cavity Doppler cooling is the cooling procedure discussed above, cavity sideband cooling is used to cool free particles when they are strongly confined in LD regime [36]. Chuah et al [37] investigate the dynamics of cavity cooling of a single ion 138 Ba + beyond the LD regime. They demonstrate the cooling to sub Doppler temperature.…”
Section: Idea Of Photoassociative Cavity Coolingmentioning
confidence: 99%
“…Cavity Doppler cooling is the cooling procedure discussed above, cavity sideband cooling is used to cool free particles when they are strongly confined in LD regime [36]. Chuah et al [37] investigate the dynamics of cavity cooling of a single ion 138 Ba + beyond the LD regime. They demonstrate the cooling to sub Doppler temperature.…”
Section: Idea Of Photoassociative Cavity Coolingmentioning
confidence: 99%
“…To improve the protect stage, a Raman technique could again be used with the Raman pump beam and the 650 nm repump laser to selectively transfer population from the S 1/2 m j = + 1 2 Zeeman sublevel to the D 3/2 protected manifold, which has been demonstrated previously. This would increase the fidelity of the protect stage from 50% to ∼90% [21].…”
Section: Potential Apparatus Improvementsmentioning
confidence: 99%
“…Rather than using a narrow quadrupole transition, one can also sideband cool using a Raman transition, tailored to be narrow by choices of detuning and Rabi frequencies [20], between two quantum states, e.g., electronic [21], hyperfine [22][23][24][25], or Zeeman levels [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First indications that this might indeed be the case were found in Paris already more than twenty years ago [5]. More systematic experimental studies of cavity-mediated laser cooling have subsequently been reported by several groups [6][7][8][9][10][11][12][13][14]. All of these experiments have their respective merits.…”
Section: Introductionmentioning
confidence: 99%